PTSD is associated with structural changes in the neural connections between the right and left hippocampus - Assonov, Дмитро (Psychosomatic Medicine and General Practice, 2020)
A multi-cohort analysis of the diffusion magnetic resonance imaging (dMRT) results of 3047 people from 28 cohorts, conducted by a large group of researchers from 92 scientific institutions found that PTSD is associated with structural changes in the tapetum, connecting the right and left hippocampus. These changes may explain the hippocampal dysfunction associated with behavioral and cognitive symptoms of PTSD.